2011
DOI: 10.1111/j.1467-9361.2011.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Business Cycle Synchronization in the Proposed East African Monetary Union: An Unobserved Component Approach

Abstract: This paper uses the business cycle synchronization criteria of the theory of optimum currency area (OCA) to examine the feasibility of the East African Community (EAC) as a monetary union. We also investigate whether the degree of business cycle synchronization has increased after the 1999 EAC Treaty. We use an unobserved component model to measure business cycle synchronization as the proportion of structural shocks that are common across different countries, and a time-varying parameter model to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
(25 reference statements)
1
18
0
1
Order By: Relevance
“…Falagiarda (2010) has suggested that, whereas a common currency area in the region is a viable option, there are some statistical and country-specific anomalies that raise some doubts on quality of findings. Additionally, Kishor and Ssozi (2011) have used synchronization of the business cycle as criteria of optimum currency area to conclude that, while the rate of harmonization has increased since the EAC Treaty was enforced in the year 2000, the degree of interrelatedness is still relatively weak, given that the proportion of shocks common to candidate states is still small. On the same basis of business cycle co-ordination, Sheik et al (2011) have used extracted business trends and cycles to examine correlations and variances of annual GDP data.…”
Section: The Proposed East African Monetary Union (Eamu)mentioning
confidence: 99%
See 1 more Smart Citation
“…Falagiarda (2010) has suggested that, whereas a common currency area in the region is a viable option, there are some statistical and country-specific anomalies that raise some doubts on quality of findings. Additionally, Kishor and Ssozi (2011) have used synchronization of the business cycle as criteria of optimum currency area to conclude that, while the rate of harmonization has increased since the EAC Treaty was enforced in the year 2000, the degree of interrelatedness is still relatively weak, given that the proportion of shocks common to candidate states is still small. On the same basis of business cycle co-ordination, Sheik et al (2011) have used extracted business trends and cycles to examine correlations and variances of annual GDP data.…”
Section: The Proposed East African Monetary Union (Eamu)mentioning
confidence: 99%
“…(ii) an anti-thesis on papers that have recommended against the common currency area (Buigut, 2011;Rusuhuzwa & Masson, 2012;Davoodi et al, 2013;Mafusire & Brixiova, 2013;Lepetit et al, 2014;Asongu, 2014bc) and (iii) a synthesis for inquiries that have presented a case for the monetary zone, contingent on substantial policy efforts from candidate countries (Buigui & Valev, 2005 ;Falagiarda, 2010;Kishor & Ssozi, 2011;Sheik et al, 2011). From an initial assessment, like with the case of the WAMU, we find that empirical results and corresponding recommendations differ by authors, periodicity, sampled countries and methodology.…”
Section: The Proposed East African Monetary Union (Eamu)mentioning
confidence: 99%
“…Examples include Drummond et al . (), Mafusire and Brixiova (), Kishor and Ssozi () and Buigut and Valev ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…We summarise in Table empirical studies on the proposed EAMU in a chronology that is consistent with Hegelian dialectics, notably: (i) a thesis on studies presenting a case for the monetary union (Mkenda, ; Bangaké, ; Asongu, ), (ii) an anti‐thesis on papers that have recommended against the common currency area (Buigut, ; Rusuhuzwa and Masson, ; Davoodi et al ., ; Mafusire and Brixiova, ; Lepetit et al ., ; Asongu, , ) and (iii) a synthesis for inquiries that have presented a case for the monetary zone, contingent on substantial policy efforts from candidate countries (Buigui and Valev, ; Falagiarda, ; Kishor and Ssozi, ; Sheik et al ., ). From an initial assessment, as with the case of the WAMU, we find that empirical results and corresponding recommendations differ by authors, periodicity, sampled countries and methodology.…”
Section: The Proposed East African Monetary Union (Eamu)mentioning
confidence: 99%